Second language learner's access to parameters of Universal Grammar: a syntactic perspective - Saeipoor, Neda; Mustapha, Ghazali; Ismail, Ismi Arif; Krauss, Steven Eric (Universiti Putra Malaysia Press, 2011)
In Universal Grammar, syntax is explained through X-bar theory. X-bar theory is the component of Universal Grammar which specifies the hierarchical structure of the heads of phrases, their specifiers and complements. Investigating the availability of this component in adults learning a second language can provide a better insight into the process of second language learning. This study attempted to find out if the X-bar theory is accessible to Malay speaking adults learning English as a second language and to investigate the possible developmental stages of syntactic knowledge, with regards to Malay adult second language learners writing in English. The data show that the learners can apply the word-order parameter and the null-subject parameter in their spontaneous writing at earlier stages. This implies the availability of the VP-related nodes of the X-bar tree at the first stage of learning grammar. The IP-related agreement parameter and the CP-related auxiliary movement emerge later as the learners become more and more proficient in the second language.